STRATEGI KOMUNIKASI PUBLIK BAZNAS BAZIS DKI JAKARTA PADA INSTAGRAM @BAZNASBAZISDKIJAKARTA - Darajat, Deden Mauli; Rahmi, Cinta (Jurnal Kommunity Online, 2023)
This article discusses the public communication strategy carried out by the National Amil Zakat Agency (Baznas) of the DKI Jakarta Province Amil Zakat Infak Alms (Bazis) Agency which is carried out through Instagram media. This study uses a library research research method which is carried out by referring to journal articles, repositories, social media reports and all resources that can be accessed online with a qualitative descriptive design approach. The findings in this study are that the Public Communication strategy on Instagram carried out by Baznas Bazis DKI Jakarta is firstly Instagram as an effective medium, second, messages from figures, third, showing current trends, fourth, approach for singles, fifth, Friday blessing campaign. , sixth, weekend entertainment, seventh, pick-up service, outlets, up to official zakat cash, and eighth, alms to refuse the plague. The communication strategy carried out by Baznas Bazis DKI is part of the zakat campaign and dissemination of information related to zakat both to muzakki and mustahik with the Instagram social media approach.